The Principle of Balance Formulation as the Basis for Cancellation of Agreement in Indonesia (Lex Scientia Law Review, 2022)
This study aims to examine the essence of the principle of balance in the agreement and dissect the position of the principle of balance as the legal reason for the cancellation of an agreement in order to realize equitable law in Indonesia. The research method used in this research is doctrinal research by using a statutory approach, a conceptual approach, and a comparative approach. Based on the research conducted, it was found that the essence of the principle of balance is a principle that emphasizes the existence of balance or equality of the rights and obligations of the parties in an agreement. Furthermore, the principle of balance can be used as a reason to cancel an agreement in Indonesia that has fulfilled the conditions for a valid agreement in Article 1320 jo 1338 of the Indonesian Civil Code as long as it is interpreted in the form of abuse of circumstances.